Effects of a mental health nursing simulation for general ward nurses: A pilot study - Min‐Yeong Lee; Yun‐Jung Choi (Wiley, 2023)
Abstract This study aimed to develop a mental health nursing simulation education programme for non‐psychiatric nurses and verify its effects on mental health care competence, burden, and anxiety. To verify the effects of the simulation, we applied a non‐equivalent control group pre‐posttest research design. We developed a mental health nursing simulation using a standardized patient who presented moderate levels of anxiety and depressive mood during chemotherapy after mastectomy. The participants were nurses working at non‐psychiatric wards of a general hospital in Seoul, Korea. Participants' mental health care competency scores increased by 80% in the experimental group and 15% in the control group from pre‐test to posttest. Burden scores decreased by 42% in the experimental group and 4% in the control group from pre‐test to posttest, and anxiety scores decreased by 77% in the experimental group and 24% in the control group. This study demonstrated the nursing simulation education programme's effectiveness as a complementary tool to improve mental health nursing care for non‐psychiatric nurses.